A joint Roman Space Telescope and Rubin Observatory synthetic wide-field imaging survey. Issue 2 (13th March 2023) - Troxel, M A; Lin, C; Park, A; Hirata, C; Mandelbaum, R; Jarvis, M; Choi, A; Givans, J; Higgins, M; Sanchez, B; Yamamoto, M; Awan, H; et al.
ABSTRACT: We present and validate 20 deg 2 of overlapping synthetic imaging surveys representing the full depth of the Nancy Grace Roman Space Telescope High-Latitude Imaging Survey (HLIS) and 5 yr of observations of the Vera C. Rubin Observatory Legacy Survey of Space and Time (LSST). The two synthetic surveys are summarized, with reference to the existing 300 deg 2 of LSST simulated imaging produced as part of Dark Energy Science Collaboration (DESC) Data Challenge 2 (DC2). Both synthetic surveys observe the same simulated DESC DC2 universe. For the synthetic Roman survey, we simulate for the first time fully chromatic images along with the detailed physics of the Sensor Chip Assemblies derived from lab measurements using the flight detectors. The simulated imaging and resulting pixel-level measurements of photometric properties of objects span a wavelength range of ∼0.3–2.0  μ m. We also describe updates to the Roman simulation pipeline, changes in how astrophysical objects are simulated relative to the original DC2 simulations, and the resulting simulated Roman data products. We use these simulations to explore the relative fraction of unrecognized blends in LSST images, finding that 20–30 per cent of objects identified in LSST images with i -band magnitudes brighter than 25 can be identified as multiple objects in Roman images. These simulations provide a unique testing ground for the development and validation of joint pixel-level analysis techniques of ground- and space-based imaging data sets in the second half of the 2020s – in particular the case of joint Roman–LSST analyses.